2018
DOI: 10.1177/0143034318817078
|View full text |Cite
|
Sign up to set email alerts
|

Development of curriculum-based measurements in mathematical computations for Arab-speaking fourth grade students

Abstract: In the Arab region, several assessments are available to evaluate student skills in mathematical computations. However, none of them uses formative evaluation to guide universal screening of struggling learners or students with learning disability (LD). The current study aimed to develop mathematical computation curriculum-based measurement (MC-CBM) for Arab speaking fourth grade students, examine its psychometric properties, test its adequacy for use in an Arab context, namely Oman, determine an adequate time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…On the other hand, the results of this study disagree with that of [12], who indicated that the percentage of health fields covered by general science textbooks for the fifth, sixth, and seventh grades of the basic stage in Palestine reached 72.7% and the percentage of environmental fields covered reached 66.7%. It also disagreed with a study by Al-Shehhi, Emam, Al-Otaiba, Ibrahim, and Al-Mehrizi [19], which reported that the effectiveness of promoting the healthy behavior of the -science curriculum developed for the first grade in Jordan was rated moderately in most evaluation indicators by supervisors and teachers.…”
Section: Discussionmentioning
confidence: 63%
“…On the other hand, the results of this study disagree with that of [12], who indicated that the percentage of health fields covered by general science textbooks for the fifth, sixth, and seventh grades of the basic stage in Palestine reached 72.7% and the percentage of environmental fields covered reached 66.7%. It also disagreed with a study by Al-Shehhi, Emam, Al-Otaiba, Ibrahim, and Al-Mehrizi [19], which reported that the effectiveness of promoting the healthy behavior of the -science curriculum developed for the first grade in Jordan was rated moderately in most evaluation indicators by supervisors and teachers.…”
Section: Discussionmentioning
confidence: 63%
“…In my future work, I will be the teacher and can rank each item with (+, 0, -) besides a more qualitative evaluation. This was done in a study by Al-Shehhi et al (2019).…”
Section: Content Validitymentioning
confidence: 99%